Implementasi Kurikulum Pai Di Min 1 Kutai Timur Sangatta Utara - Maria Nur Viona Mahwiz; Binti Fatimatul Khoiriyah; Anjani Putri Belawati Pandiangan (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This research examines the implementation of the Islamic Religious Education (PAI) curriculum at MIN 1 Kutai Timur, North Sangatta. The objective of this study is to understand how the PAI curriculum is applied and its impact on the development of students' character. The research method employed is qualitative with a case study approach, involving data collection through observations, interviews, and document analysis. The findings indicate that the PAI curriculum at MIN 1 Kutai Timur is designed not only to enhance students' cognitive skills but also to shape their moral and spiritual values. The curriculum implementation involves a holistic approach that integrates religious knowledge with personal experiences and the students' social context, thereby making learning more meaningful and relevant. Furthermore, the active participation of teachers and adequate facility support are crucial to the successful implementation of this curriculum. In conclusion, this study demonstrates that the implementation of the PAI curriculum at MIN 1 Kutai Timur has effectively developed students who are not only intellectually capable but also possess commendable character, tolerance, inclusiveness, and an appreciation for diversity. This curriculum is expected to cultivate a generation that contributes positively to society and upholds universal human values.